Pengaruh Hedonic Shopping Motive dan Visual Merchandising terhadap Impulse Buying dengan Shopping Lifestyle sebagai Variabel Intervening pada Konsumen Shopee di Kota Mataram - Tita Astiani; Riduan Mas’ud; Taufiq Gozi (PALAPA, 2023)
With exists the development of fashion Of course It just has a big impact on the people who want it No Want to must follow existing trends, for all circles, especially in circles generation young. Next, there are advances in media that can said to the more advanced for example print media or electronic media, so the internet has an role important in sourcing information to the public about the latest fashion trends. Study This aims To test and analyze the influence of Hedonic Shopping Votive and Visual Merchandising on Impulse Buying with ShoppingLifestyle as a variable affecting Shopee consumers in Mataram City. Population in study This is consumers who use it Shopee platform. Taking samples with the technique of purposive sampling. Amount respondents is 100. The analysis technique used is SEM-PLS with Smart PLS 3.0 software. Research results This finds that there exists influence in a way directs Hedonic Shopping Motive and Shopping Lifestyle towards Impulse Buying, only Visual Merchandising is not influential in a way direct to Impulse Buying. Hedonic Shopping Motive and Visual Merchandising are not influential in a way direct to Impulse Buying. Shopping Lifestyle is not capable of becoming a liaison between Hedonic Shopping Motive and Visual Merchandising towards Impulse Buying consumers in shops on the Shopee platform.